Mechanical behavior of glass fiber polyester hybrid composite filled with natural fillers. (September 2016) - Gupta, G; Gupta, A; Dhanola, A; Raturi, A
Abstract: Now-a-days, the natural fibers and fillers from renewable natural resources offer the potential to act as a reinforcing material for polymer composite material alternative to the use of synthetic fiber like as; glass, carbon and other man-made fibers. Among various natural fibers and fillers like banana, wheat straw, rice husk, wood powder, sisal, jute, hemp etc. are the most widely used natural fibers and fillers due to its advantages like easy availability, low density, low production cost and reasonable physical and mechanical properties This research work presents the effect of natural fillers loading with 5%, 10% and 15% on mechanical behavior of polyester based hybrid composites. The result of test depicted that hybrid composite has far better properties than single fibre glass reinforced composite under impact and flexural loads. However it is found that the hybrid composite have better strength as compared to single glass fibre composites.